A Cross-cultural ethnobotanical knowledge comparison about local plants among Pashto, Punjabi and Saraiki communities living in Southwest Pakistan - Shiekh Zain Ul Abdin; Khan, Raees; Ahmad, Mushtaq; Jan, Hammad Ahmad; Zafar, Muhammad; Shah, Abdul Haleem (Ethnobotany Research and Applications, 2022)
Background: The current work was conducted with the aim for the documentation of the indigenous uses of medicinal plants for food purposes across the three main indigenous communities in South-west Pakistan. Field work was conducted in 21 villages belonging to the three regions of the district D.I. Khan (Saraiki Community), district Zhob (Pashto Community) and district Mianwali (Punjabi Community), located in the Southwest Pakistan. Methods: Snowball sampling method was used to interview 93 informants (43 Pashto, 28 Punjabi and 22 Saraiki) using semi-structured questionnaire to document the uses of indigenous taxa as food, herbal tea and herbal juice/drinks purposes. Documented data was quantified by indices UV (use value) and CI (Cultural importance values). Results: Overall, 68 Plants species belonging to the 40 families were documented to be used in food, herbal tea and herbal juice/drinks. The most important species was Limonium cabulicum on the basis of use reports. Major ailments include stomach problems, hair loss, wounds, fever, weight loss and others treated with traditional food /drinks. The Phyllanthus emblica (0.31) has the highest UV. The highest cultural value was obtained for Zingiber officinale (0.28). Conclusion: The traditional communities still use medicinal plants. Cross-cultural ethnobotanical studies are fundamental among three ethnic communities in Southwest Pakistan not only for suggesting customs of using plant-based products, which could be exploited in sustainable local development projects (e.g. trade of wild medicinal herbs on small-scale, herbal products, food niche and also focusing on eco-tourism), but also for development relationship and reconciliation among diverse ethnic communities. Keywords: Cross-Cultural Ethnobotany, food plants, herbal tea, herbal juice/drinks, Pashto, Punjabi, Saraiki